Female phenotype and multiple abnormalities in sibs with a Y chromosome and partial X chromosome duplication: H--Y antigen and Xg blood group findings. Issue 4 (August 1980) - Bernstein, R; Jenkins, T; Dawson, B; Wagner, J; Dewald, G; Koo, G C; Wachtel, S S
Abstract : A mentally retarded female child with multiple congenital abnormalities had an abnormal X chromosome and a Y chromosome; the karyotype was interpreted as 46, dup(X)(p21 leads to pter)Y. Prenatal chromosome studies in a later pregnancy indicated the same chromosomal abnormality in the fetus. The fetus and proband had normal female genitalia and ovarian tissue. H--Y antigen was virtually absent in both sibs, a finding consistent with the view that testis-determining genes of the Y chromosome may be suppressed by regulatory elements of the X. The abnormal X chromosome was present in the mother, the maternal grandmother, and a female sib: all were phenotypically normal and showed the karyotype 46, Xdup(X)(p21 leads to pter) with non-random inactivation of the abnormal X. Anomalous segregation of the Xga allele suggests that the Xg locus was involved in the inactivation process or that crossing-over at meiosis occurred.